2019
DOI: 10.1186/s12983-019-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Preference of spectral features in auditory processing for advertisement calls in the music frogs

Abstract: Background Animal vocal signals encode very important information for communication during which the importance of temporal and spectral characteristics of vocalizations is always asymmetrical and species-specific. However, it is still unknown how auditory system represents this asymmetrical and species-specific patterns. In this study, auditory event related potential (ERP) changes were evaluated in the Emei music frog ( Babina daunchina ) to assess the differences in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…In addition, familiar sounds evoke smaller P3a compared with unfamiliar ones 47 . Moreover, for a given component, human-like auditory ERP components with similar stimulus responses and time windows have been found in various taxa such as primates 48 , mammals 49 , 50 , and anurans 13 , 51 – 55 . Important neuroanatomical features of brain have been conserved during vertebrate brain evolution 56 , 57 .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, familiar sounds evoke smaller P3a compared with unfamiliar ones 47 . Moreover, for a given component, human-like auditory ERP components with similar stimulus responses and time windows have been found in various taxa such as primates 48 , mammals 49 , 50 , and anurans 13 , 51 – 55 . Important neuroanatomical features of brain have been conserved during vertebrate brain evolution 56 , 57 .…”
Section: Introductionmentioning
confidence: 79%
“…The Emei music frog ( N. daunchina ) is a typical seasonal reproductive species that usually produces advertisement calls from within nest burrows in the breeding season 66 . Both behavioral and ERP studies in this species have revealed that the differences in conspecific calls are easily recognized by Emei music frogs on the basis of their different temporal and spectral acoustic characteristics 13 , 51 , 67 , 68 . For example, at the behavioral level, both male and female Emei music frogs respond strongly to conspecific calls, as well as heterospecific calls of N. hainanensis , with a slight response to the calls of N. adenopleura , while no response to the calls of N. lini 67 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…EEG might be involved in different brain functions including sensory registration, perception, movement and cognitive processes related to attention, learning, memory and decision-making (Basar et al, 2000(Basar et al, , 2001Klimesch, 1999;Mazza and Pagano, 2017). Our previous studies show that EEG bands in the Emei music frog (Nidirana daunchina) differ substantially from those of humans, especially in the high frequency band (Fang et al, 2012a); however, auditory perception in this species is closely related to dynamic activities of various EEG bands (Fang et al, 2012b) and specific event-related potentials (Fan et al, 2019;Fang et al, 2015;Yang et al, 2018;Yue et al, 2017). Because discrete brain regions are specialized for different functions (Kandel et al, 2013), it seems reasonable to hypothesize that eye preferences related to predatory responses might be associated with different activity patterns of specific EEG bands and in specific brain areas.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, the SPN could be used as a measure of expectations with voluntary attention and a tool of the research on the impact of uncertainty [ 35 , 36 , 37 ]. Interestingly, human-like auditory ERP components, with different latencies across various species for each component, have been determined in monkeys [ 38 ], cats [ 39 ], dolphins [ 40 ], rabbits [ 41 ], rats [ 42 ] and frogs [ 43 , 44 , 45 , 46 , 47 ]. Because important neuroanatomical features, including a set of brain structures that attention depends on, have been conserved during vertebrate brain evolution [ 48 , 49 , 50 ], similar ERP components across different species may indicate similar brain functions to some extent.…”
Section: Introductionmentioning
confidence: 99%